This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that the question uses an unusual notation for combinations of k from a set of n, C n k (as discussed in this wikipedia article ). For this solution, I will use the more common notation, ( k n ) .
Consider the binomial expansion of ( 1 + x ) 8 n : ( 1 + x ) 8 n = ( 0 8 n ) + ( 1 8 n ) x + ( 2 8 n ) x 2 + ( 3 8 n ) x 3 + ⋯ + ( 8 n 8 n ) x 8 n Differentiating both sides: 8 n ( 1 + x ) 8 n − 1 = ( 1 8 n ) + 2 ( 2 8 n ) x + 3 ( 3 8 n ) x 2 + 4 ( 4 8 n ) x 3 + ⋯ + 8 n ( 8 n 8 n ) x 8 n − 1 Now, let x = i : L H S = 8 n ( 1 + i ) 8 n − 1 = 8 n ( 2 ) 8 n − 1 ( 2 1 + 2 i ) 8 n − 1 = 8 2 n ( 2 ) 8 n − 2 [ cos ( 4 π ) + i sin ( 4 π ) ] 8 n − 1 = 2 3 2 n × 2 4 n − 1 [ cos ( 4 π ( 8 n − 1 ) ) + i sin ( 4 π ( 8 n − 1 ) ) ] = 2 n × 2 4 n + 2 [ cos ( 2 π n − 4 π ) + i sin ( 2 π n − 4 π ) ] = 2 n × 2 4 n + 2 [ cos ( − 4 π ) + i sin ( − 4 π ) ] = 2 n × 2 4 n + 2 ( 2 1 − 2 i ) = 2 4 n + 2 ( 1 − i ) n by de Moivre’s theorem R H S = ( 1 8 n ) + 2 ( 2 8 n ) i + 3 ( 3 8 n ) i 2 + 4 ( 4 8 n ) i 3 + 5 ( 5 8 n ) i 4 + ⋯ + 8 n ( 8 n 8 n ) i 8 n − 1 = ( 1 8 n ) + 2 ( 2 8 n ) i − 3 ( 3 8 n ) − 4 ( 4 8 n ) i + 5 ( 5 8 n ) + ⋯ + 8 n ( 8 n 8 n ) i 8 n − 1 = [ ( 1 8 n ) − 3 ( 3 8 n ) + 5 ( 5 8 n ) + ⋯ − ( 8 n − 1 ) ( 8 n − 1 8 n ) ] + [ 2 ( 2 8 n ) − 4 ( 4 8 n ) + 6 ( 6 8 n ) + ⋯ − 8 n ( 8 n 8 n ) ] i Equating real parts: 2 4 n + 2 n ∴ 2 4 n + 2 n ∴ 4 2 n + 1 = ( 1 8 n ) − 3 ( 3 8 n ) + 5 ( 5 8 n ) + ⋯ − ( 8 n − 1 ) ( 8 n − 1 8 n ) = n 1 0 = n 9 By inspection, this is true when n = 4